Transcriptional down-regulation of metabolic genes by Gdown1 ablation induces quiescent cell re-entry into the cell cycle - Jishage, Miki (Genes Dev, 2020)
Liver regeneration and metabolism are highly interconnected. Here, we show that hepatocyte-specific ablation of RNA polymerase II (Pol II)-associated Gdown1 leads to down-regulation of highly expressed genes involved in plasma protein synthesis and metabolism, a concomitant cell cycle re-entry associated with induction of cell cycle-related genes (including cyclin D1), and up-regulation of p21 through activation of p53 signaling. In the absence of p53, Gdown1-deficient hepatocytes show a severe dysregulation of cell cycle progression, with incomplete mitoses, and a premalignant-like transformation. Mechanistically, Gdown1 is associated with elongating Pol II on the highly expressed genes and its ablation leads to reduced Pol II recruitment to these genes, suggesting that Pol II redistribution may facilitate hepatocyte re-entry into the cell cycle. These results establish an important physiological function for a Pol II regulatory factor (Gdown1) in the maintenance of normal liver cell transcription through constraints on cell cycle re-entry of quiescent hepatocytes.